Euthanasia, Assisted Suicide, and the Philosophical Anthropology of Karol Wojtyla - Fernandes, Ashley K. (Christian bioethics, 2001)
The lack of consensus in American society regarding the permissibility of assisted suicide and euthanasia is due in large part to a failure to address the nature of the human person involved in the ethical act itself. For Karol Wojtyla, philosopher and Pope, ethical action finds meaning only in an authentic understanding of the person; but it is through acting ( actus humanus ) alone that the human person reveals himself. Knowing what the person ought to be cannot be divorced from what he ought to do; forWojtyla, the structure of the ethical “do” – the act itself – comes first. The current paper will focus on four arguments used to justify assisted suicide and euthanasia: (1) the argument from autonomy, (2) the argument from compassion, (3) the argument from the evil of suffering, and (4) the argument from the loss of dignity. It will seek to answer each claim from the perspective of Karol Wojtyla's philosophical anthropology. Much of this will come from his defining work in pure philosophy, The Acting Person (1969). The final part of the paper will suggest some positive solutions to the stalemate over the euthanasia debate, again drawn from Wojtyla's idea of human fulfillment through participation with the other, and with the community itself.